The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1074/jbc.m111.234732
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Regulation of Bile Acid Metabolism Is Associated with Improved Pathological Characteristics of the Metabolic Syndrome

Abstract: Bile acids (BAs) are powerful regulators of metabolism, and mice treated orally with cholic acid are protected from dietinduced obesity, hepatic lipid accumulation, and increased plasma triacylglycerol (TAG) and glucose levels. Here, we show that plasma BA concentration in rats was elevated by exchanging the dietary protein source from casein to salmon protein hydrolysate (SPH). Importantly, the SPH-treated rats were resistant to diet-induced obesity. SPH-treated rats had reduced fed state plasma glucose and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 82 publications
2
49
0
1
Order By: Relevance
“…The supernatant was filtered and amino acids were characterised by a Biochrom 20 plus amino acid analyser as previously described [29]. …”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was filtered and amino acids were characterised by a Biochrom 20 plus amino acid analyser as previously described [29]. …”
Section: Methodsmentioning
confidence: 99%
“…Histology Examinations-Paraffin-embedded sections of epididymal white adipose tissue (eWAT) and iWAT were stained with hematoxylin and eosin and analyzed as described previously (12). Sections of pancreatic tissue were stained for insulin, and pancreatic islet and section sizes were analyzed (13).…”
Section: Methodsmentioning
confidence: 99%
“…After 6 weeks of treatment with the respective diets, total lipid was extracted from feces collected for 48 h (12).…”
Section: Methodsmentioning
confidence: 99%
“…(A) Immunoblot analysis of CYP3A expression was performed as described in Fig dmd.aspetjournals.org although the total protein or fiber content (percentage) in the two diets is similar, the types of proteins and fibers differ by diet. Previous studies have shown that changes in dietary constituents, including fiber contents (Kritchevsky, 1978) and protein sources (Liaset et al, 2011), can influence size of the BA pool. Here, we further demonstrated, for the first time, that the change from the regular chow to the synthetic diet causes large decreases in all five major murine BAs in plasma, liver, SI, and intestinal content.…”
Section: Discussionmentioning
confidence: 99%